2012
DOI: 10.1007/s00262-011-1196-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-2 enhances immunotherapy against experimental brain tumors

Abstract: Glioblastoma multiforme is the most common and aggressive malignant brain tumor in humans and the prognosis is very poor despite conventional therapy. Immunotherapy represents a novel treatment approach, but the effect is often weakened by release of immune suppressive molecules such as prostaglandins. In the current study we investigated the effect of immunotherapy with irradiated interferon-γ (IFN-γ) secreting tumor cells and administration of the selective cyclooxygease-2 (COX-2) inhibitor parecoxib as trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…13,14 Furthermore, we previously reported that the combination of IFN-g immunotherapy and systemic COX-2 inhibition induced cure in rats with established intracerebral tumors. 15 Thus, the current study was undertaken to determine whether a GM-CSF-based immunotherapy was further enhanced by COX-2 inhibition. By applying different administration routes, we also assessed whether the therapeutic effect is dependent on the site of COX-2 inhibition.…”
mentioning
confidence: 99%
“…13,14 Furthermore, we previously reported that the combination of IFN-g immunotherapy and systemic COX-2 inhibition induced cure in rats with established intracerebral tumors. 15 Thus, the current study was undertaken to determine whether a GM-CSF-based immunotherapy was further enhanced by COX-2 inhibition. By applying different administration routes, we also assessed whether the therapeutic effect is dependent on the site of COX-2 inhibition.…”
mentioning
confidence: 99%
“…Immunotherapy per se induces an immune response associated with elevated plasma IFNγ levels and CD4 + and CD8 + T cells systemically and intratumorally (Visse et al, 2000;Eberstal et al, 2012;Fritzell et al, 2013a, b;Eberstal et al, 2014). IFNγ is predominately produced by activated T cells and thus, intratumorally implanted MSCs are most likely exposed to significant levels of IFNγ.…”
Section: Discussionmentioning
confidence: 97%
“…The cells have been transduced to express IFNγ (N32-IFNγ) (Visse et al, 1999) and both cell lines were cultured as described elsewhere (Eberstal et al, 2012).…”
Section: Cellsmentioning
confidence: 99%
“…Inhibition of MDSC accumulation was associated with elevated levels of CXCL10 and cytotoxic T lymphocytes in the TME [68]. Studies have looked at the efficacy of combining COX2 inhibitor celecoxib in combination with immunotherapy [119], dendritic cell vaccination [120], CD40 monoclonal antibody [121] with moderate to good success. GMCSF was upregulated in both human and mouse glioma TME and Kohanbash et al showed that GMCSF induced IL-4Rα expression on MDSCs in the glioma TME, that in turn induced arginase expression in response to IL-13 [80].…”
Section: Mdscs In Gliomamentioning
confidence: 99%